Epidemiological Aspects of Occupational Exposure to Sharp tools among Nurses in a Military Hospital in Tehran, Iran - Norouz Mahmodi; Mojtaba Sepandi; Amir Sheikh Mohammadi; Dr. Hossein Masoumbeigi (Iranian Journal of Health, Safety and Environment, 2015)
The most frequent way of transmission of various diseases such as HBV, HIV and HCV is exposure to sharp tools. The purpose of the study was to determine the epidemiological aspects of occupational exposure and risk factors of injuries from sharp tools among nurses in a military hospital. In this cross - sectional study 100 nursing staff in a military hospital was chosen as sample. Personal and professional information collected by a valid and reliable questionnaire, and data were analyzed using SPSS 17 software.The prevalence of occupational exposure to sharp tools of hospital waste was 41 %. Mean age and mean of experience years in nurses were 34.7 ± 5.88 and 10.99 ± 5.52 year respectively. About 63% of nurses in disaster reported the matter to the Committee on Hospital Infection Control.Most affected by the syringe needle was 46.3%. Working load and needle recapping were the main causes of the damage due to exposure to the sharp objects, 26.8 and % 31.7 respectively. The relationship between occupational exposure to hospital sharp tools and age, experience, education and place of work was significant with P= 0.006, 0.017, 0.027 and 0.008 respectively. According to the complications of sharp tools, reduction of sharp components requires regular training courses for staff, proportion of the number of work shifts, strict implementation of treatment protocols, modification of the current inaccuracy procedures, access to adequate equipment's and safe and an effective mechanism for reporting of occupational accidents in all of the sectors.